In vivo CNS Activity of Methanolic Extract of Ficus racemosa Fruits in Experimental Animals (Bangladesh Pharmaceutical Journal, 2018)
The purpose of the study was to evaluate the CNS activity of the methanolic extract of Ficus racemosa fruits. The powdered fruits of F. racemosa were extracted with methanol to investigate the effect on central nervous system in Swiss albino mice. The CNS depressant activity was evaluated by observing the reduction of locomotor activity by open field and hole cross tests. The anti-depressant activity was tested by forced swimming and tail suspension methods. For CNS activity, two test doses of the extracts such as 200 and 400 mg/kg body weight were used. However, the extracts showed significant dose dependent CNS depressant activity when compared to the control in animal models. From our research, it can be concluded that the methanolic extract of F. racemosa fruits possesses significant CNS depressant activity. So, further studies are recommended for the isolation of compounds responsible for this activity.Bangladesh Pharmaceutical Journal 21(2): 139-144, 2018